2016
DOI: 10.1002/2211-5463.12002
|View full text |Cite
|
Sign up to set email alerts
|

A specific role for PRND in goat foetal Leydig cells is suggested by prion family gene expression during gonad development in goats and mice

Abstract: Three genes of the prion protein gene family are expressed in gonads. Comparative analyses of their expression patterns in mice and goats revealed constant expression of PRNP and SPRN in both species and in both male and female gonads, but with a weaker expression of SPRN . By contrast, expression of PRND was found to be sex‐dimorphic, in agreement with its role in spermatogenesis. More importantly, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…PrP C has been detected in the Sertoli cells of immature goat bucks (130 days post conception) and in ejaculated buck spermatozoa (Allais-Bonnet et al, 2016 ). Levels of PRNP mRNA were high in buck testicular tissue from birth and gradually decreased to reach a steady level at puberty.…”
Section: Discussionmentioning
confidence: 99%
“…PrP C has been detected in the Sertoli cells of immature goat bucks (130 days post conception) and in ejaculated buck spermatozoa (Allais-Bonnet et al, 2016 ). Levels of PRNP mRNA were high in buck testicular tissue from birth and gradually decreased to reach a steady level at puberty.…”
Section: Discussionmentioning
confidence: 99%
“…1 Meanwhile, several polymorphisms of PRND gene had been shown to influence the goat early sex differentiation 2 as well as ram fertility, 3 especially affecting the differentiation of goat foetal leydig cells. 4 Remarkably, at present, there is no study that reveals the relationship of the insertion/deletion (indel) polymorphisms of PRND gene with scrapie susceptibility or growth traits in sheep.…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous study also has demonstrated the feasibility and high efficiency of the ME method in low-frequency detection. 5 To detect the possible indel of sheep PRND gene by using ME method, a total of 623 sheep from the 4…”
Section: Introductionmentioning
confidence: 99%